Principles of the Textbook Elaboration «English for Civil Engineering Students» - Liudmyla Byrkun; Nataliia Kuzlo (Pedagogical Discourse, 2017)
The necessity of teaching English for professional purposes and specifically in the area of construction is irrefutable. Language proficiency is very important and essential in all professional fields specifically in construction industry due to its specific nature and concepts. English for Specific Purposes has become one of the main domains of English language teaching. ESP used to be seen as a separate field within English language teaching, yet it proved to be inseparable by any means. The study tried to reveal some principles of textbook elaboration for future civil engineers within English for specific purposes. The principles of English for specific purposes for civil engineering students’ textbook elaboration have been highlighted in the article. The attention has been focused on the principles of communicative-cognitive approach for foreign languages teaching in correlation with separate principles of educational published paper’s major conceptual bases. Such principles as principle of scientific approach, principle of cyclic textbook structure and principle of usage communicative-cognitive approach have been explained on the sample of the textbook. In this study, the literature related to the principles of textbook elaboration was examined and the application of the author’s model based on its practical application is explained. Regarding the students’ satisfaction of the textbook «English for civil engineering students» based on the students’ opinion and achievements, the context of English for specific purposes gained high score. Results that have been obtained in this study are recommended for implementation in the process of English for specific purposes learning.